Pembinaan dan Pelatihan Olimpiade Sains Nasional (OSN) Bidang Biologi pada Siswa SMAN 1 Tualang, Kabupaten Siak, Provinsi Riau - Fajrin, Rahmat (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2024)
Advancing to the national level in the National Science Olympiad (OSN) is a significant challenge faced by many schools, given the tight competition and high standards of ability that must be achieved by students to compete at that level. SMAN 1 Tualang, as one of the leading high schools in Siak Regency, has consistently succeeded in sending its students to the provincial level every year. However, in the field of biology, students still face difficulties in continuing the competition to the national level. The purpose of this coaching and training activity is to prepare students to face the OSN with adequate knowledge and skills to be able to compete at the national level. This activity is carried out through the method of providing direct material and discussing questions using the drilling method. The results of this activity show an increase in students' ability to solve OSN questions in the field of biology, which can be seen from the increase after coaching and training with an N-gain value of 0.58, which is included in the moderate category. Thus, this activity is effective in improving students' readiness to face the national science Olympiad and is recommended to be implemented continuously for more optimal results. Melaju ke tingkat nasional dalam Olimpiade Sains Nasional (OSN) merupakan tantangan signifikan yang dihadapi oleh banyak sekolah, mengingat persaingan yang ketat dan tingginya standar kemampuan yang harus dicapai oleh peserta didik untuk bersaing di jenjang tersebut. SMAN 1 Tualang, sebagai salah satu SMA unggulan di Kabupaten Siak, berhasil secara konsisten mengirimkan siswanya ke tingkat provinsi setiap tahun. Namun, pada bidang biologi, siswa masih menghadapi kesulitan untuk melanjutkan kompetisi ke jenjang nasional. Tujuan dari kegiatan pembinaan dan pelatihan ini adalah untuk mempersiapkan siswa-siswi menghadapi OSN dengan bekal pengetahuan dan keterampilan yang memadai agar mampu bersaing di tingkat nasional. Kegiatan ini dilakukan melalui metode pemberian materi secara langsung dan pembahasan soal menggunakan metode drilling. Hasil dari kegiatan ini menunjukkan adanya peningkatan kemampuan siswa dalam menyelesaikan soal OSN bidang biologi, yang terlihat dari peningkatan setelah pembinaan dan pelatihan dengan nilai N-gain sebesar 0,58 termasuk kategori sedang. Dengan demikian, kegiatan ini efektif dalam meningkatkan kesiapan siswa dalam menghadapi Olimpiade sains nasional dan direkomendasikan untuk diimplementasikan secara berkelanjutan untuk hasil yang lebih optimal.